UJI AKTIVITAS IMUNOSTIMULATOR FRAKSI ETIL ASETAT EKSTRAK ETANOL KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) TERHADAP PROLIFERASI SEL LIMFOSIT MENCIT GALUR SWISS SECARA IN VITRO BESERTA IDENTIFIKASI KANDUNGAN SENYAWA KIMIANYA - Ulfah, Maria; Nirmalasari, Nirmalasari; Sasmito, Ediati (e-Publikasi Ilmiah Fakultas Farmasi Unwahas Semarang, 2013)
ABSTRACTImmunostimulatory agent has an important role in the treatment of infectious disease caused bypathogen. Roselle calyx (Hibiscus sabdariffa Â immune system. The aims of this research was to know immunostimulatory activity of ethyl acetate fraction ofethanolic extract of roselle calyx on lymphocyte cell proliferation swiss strain mice and to identified thechemical compounds of the fraction.Roselle calyx was ext racted by maceration method using ethanol 96% as a solvent. The ethanolicextract was partitioned gradually by n-hexan and ethyl acetate. Series of ethyl acetate fraction were made toconcentration 10, 20, 50, 100, 200, 400 Î¼g/mL and positive control PHA 10 Î¼g/mL for tested to lymphocyte cellculture. Immunostimulatory act ivity test was done according to MTTAssay Â Key words : roselle calyx, ethyl acetate fraction, MTTAssayÂ , immunostimulatorymethod. Lymphocyte proliferat ionÂ activity was analyzed statistically to the value of Optical Density (OD) result of the Enzyme LinkedImmunosorbent Assay (ELISA) reader using Kruskal Wallis Test continued by Mann Whitney Test (p<0,05).Identificat ion of the contents phenolic compounds and flavonoids performed by Thin Layer Chromatography(TLC).The result of the research showed that ethyl acetate fraction had lymphocyte cell proliferation activity atthe concentration of 50, 100, 200, and 400 Î¼g/mL. The ethyl acetate fraction of roselle calyx contained phenoliccompounds and flavonoids.L.) used by community as a health drink to enhance bodyâs